Association between knowledge, attitude and practice on cardiovascular disease among early adults of Lucknow city - Bhawana Dayal; Neetu Singh (Al Ameen Medical College, 2018)
Introduction: CVD has been designated as the leading cause of mortality and morbidity, representing a total of 31% of all global deaths. Aim: This research aimed to determine the association between Knowledge, attitude and practice regarding CVD among early adults of Lucknow city. Methods: Using descriptive statistics and Pearson's coefficients correlation, a convenience sample of 250 adults was used. Data was collected using a standardized questionnaire. Results: Majority belonged to low level knowledge category (65.20%) to the least falling in High category (12.40%). The total mean score for knowledge associated with other risk factors is 9.060 ± 4.805 scores ranging from 0 to 20. The mean score for attitude was 11.82±5.032, 37.6% score ranging from 0 to 19 and for practice, scores ranged from 3 to 15 (mean=8.93; SD=2.2), 87.60% of the respondents scored in the poor practice range. None of the respondents fell in the category of Good practice. There was a significant correlation between all the three components that is Knowledge, attitude and practice at p<.01 level of significance. Conclusion: The positive results obtained in this study can give future scope to policy implementers to work in this area for eradicating disease by working on these areas.